1863-64 Utah Laws 47, To Incorporate The City Of Payson, § 27 - (:unkn) unknown (My University, 1864)
To direct or prohibit the location and management of houses for the storing of gunpowder, tar, pitch, resin or other combustible and dangerous materials within the city, and to regulate the conveying of gunpowder.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER